Are human ATP-binding cassette transporter C11 and earwax associated with the incidence of cholesteatoma?. (May 2018) - Nakagawa, Hiroshi; Toyoda, Yu; Albrecht, Tobias; Tsukamoto, Megumi; Praetorius, Mark; Ishikawa, Toshihisa; Kamiya, Kazusaku; Kusunoki, Takeshi; Ikeda, Katsuhisa; Sertel, Serkan
Abstract: Cholesteatoma is an ear disease based on a locally destructive noncancerous conglomerate of epidermis and keratin debris. Abnormal growth of stratified keratinized squamous epithelium in the temporal bone causes destruction of the outer and middle ear, potentially leading to hearing impairment, facial palsy, vertigo, lateral sinus thrombosis, and intracranial complications. Although cholesteatoma is effectively treated by surgical resection (mastoidectomy), the lack of effective and nonsurgical therapies potentially results in fatal consequences, establishing the need for a comprehensive investigation of cholesteatoma pathogenesis. Although its etiology is still being debated, interestingly, we found that the trend associated with the 538G allele frequency of the adenosine triphosphate-binding cassette transporter C11 ( ABCC11 ) gene, the determinant of wet-type earwax, and ethnic groups was similar to that between the incidence of cholesteatoma and ethnic groups (countries). The incidences of cholesteatoma in Europe (Denmark, Finland, and Scotland) are higher than in East Asia (Japan), and the frequencies of the ABCC11 538G allele in African, American, and European (Finland and Scotland) populations are higher than those in East Asian populations (Japan). Additionally, a single-nucleotide polymorphism in the ABCC11 gene (rs17822931, 538G > A; Gly180Arg) is closely related to earwax morphotypes. While earwax is often beneficial to ear health, it is sometimes harmful in cases where it causes hearing impairment. Based on independent findings of associations between ABCC11 and the physiological environment of the auditory canal, we hypothesize a possible link between ABCC11, earwax, and the incidence of cholesteatoma.